A lark for the sake of their country : the 1926 General Strike volunteers in folklore and memory - Saltzman, Rachelle Hope (Manchester University Press, 2012)
This work tells the tale of the upper and middle-class volunteers in Great Britain's 1926 General Strike. With behaviour derived from their play traditions - the larks, rags, fancy dress parties, and treasure hunts that prevailed at universities and country houses - they transformed a potential workers' revolution into a festive public performance of Englishness. The author recreates the cultural context for the volunteers' actions to explore how volunteers, strikers, and the Government used the strike to define national identity; it also considers how scholars, novelists, playwrights, diarists, museum curators, local examine historians, and even a theme restaurant have continued to recycle the event.